Freedom for Themselves : North Carolina's Black Soldiers in the Civil War Era - Reid, Richard M., 1943- (Book collections on Project MUSE., 2008)
More than 5,000 North Carolina slaves escaped from their white owners to serve in the Union army during the Civil War. Richard Reid explores the stories of black soldiers from four regiments raised in North Carolina. Constructing a multidimensional portrait of the soldiers and their families, he provides a new understanding of the spectrum of black experience during and after the war.